Translation and norms - Schäffner, Christina (Multilingual Matters, 1999)
Translation norms are understood as internalized behavioural constraints which embody the values shared by a community. In the two main contributions it is argued that all decisions in the translation process are primarily governed by norms. The explanatory power of a norm-based theory of translation is then critically reflected upon in the debates and the responses.